(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2021)
This article is the result of an exploratory research on the thinking and writing of Carlos Huayquiñir Rain (1913-1978), a self-taught journalist who wrote about the Mapuche people between the 1930s and 1960s. Its purpose is to analyze two central topics that emerge of the prose of Huayquiñir arranged in the Mapuche press of the referred years. On the one hand, the call for instruction and education for mapuche children made by the author; on the other, his fight against racism manifested in the press, politicians and school institutions. The article stems from an investigation carried out in the Hemeroteca of the National Library of Chile, plus the work in private archives. It hopes to contribute to the knowledge about this Mapuche author.